1984
DOI: 10.1080/15287398409530509
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies comparisons of particle deposition and mucociliary clearance in tracheobronchial airways

Abstract: Inhaled insoluble particles that deposit along normal healthy tracheobronchial airways of humans and other mammals are transported on the proximally moving mucous lining to the larynx, where they are swallowed. The transit time from the most distal ciliated airways varies from 0.1 to 1 d, with each individual having a relatively constant, characteristic time. The exact time course of clearance depends on the distributions of both particle deposition and mucus velocities along the airways. There are too few dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(43 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…There was very little overlap between the lethal and 'safe' doses, and the estimated LD 50 of ricin in mice was approximately 4 μg/kg, in agreement with the published value of 3-5 μg/kg [ 9 ]. Histopathological analysis of the lungs (including the trachea and alveoli) from the mice showed necrosis of alveolar cells, indicating that the aerosol particles were small enough (1-2 μm) to penetrate to the aveolar region of the lung [ 20 ] (data not shown).…”
Section: The Aerosol Challenge Routesupporting
confidence: 85%
See 1 more Smart Citation
“…There was very little overlap between the lethal and 'safe' doses, and the estimated LD 50 of ricin in mice was approximately 4 μg/kg, in agreement with the published value of 3-5 μg/kg [ 9 ]. Histopathological analysis of the lungs (including the trachea and alveoli) from the mice showed necrosis of alveolar cells, indicating that the aerosol particles were small enough (1-2 μm) to penetrate to the aveolar region of the lung [ 20 ] (data not shown).…”
Section: The Aerosol Challenge Routesupporting
confidence: 85%
“…It has been suggested that hepatocellular and renal lesions are the result of toxin induced vascular damage rather than organ damage per se [ 3 ], but we rarely observe such lesions. We postulate that death is more likely due to severe hypoglycemia, as reported by Pincus et al [ 20 ]. With regard to the toxicity of aerosolized ricin, it is not entirely clear how death is caused, though it is likely to be related to a large extent to damage in the lung [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…differences in breathing patterns, obligate nose-breathing and the physics of the aerosols delivered [74]. Overall it would appear that the airway anatomy and oral breathing of humans tends to lead to a greater amount of upper bronchial airway particle deposition and to greater deposition on localized surfaces near airway bifurcations compared to smaller mammals [75]. Table 4 shows the morphometric characteristics of cells in the alveolar region of the lungs of rats, dogs, baboons and humans [76] .…”
Section: Rational Model Selectionmentioning
confidence: 99%
“…Small changes in NMC related to cyclic changes in nasal passage volume are also unlikely to account for the effects seen. Upper respiratory responses to numerous toxicants are qualitatively similar between humans and many experimental animals (10,20,21), and the mechanisms of mucociliary clearance are thought to be similar in humans and most other mammals. Animal studies have shown that low-level irritant exposure accelerates mucociliary clearance.…”
Section: Resultsmentioning
confidence: 90%